Fabry’s disease in a female carrier with bilateral thalamic infarcts: a case report and a family study - Castro, Luiz Henrique Martins; Monteiro, Mario Luiz Ribeiro; Barbosa, Egberto Reis; Scaff, Milberto; Canelas, Horacio Martins (São Paulo Medical Journal, 1994)
An unusual case of a young woman, heterozygote for Fabry gene is reported, who presented bilateral thalamic infarcts due to occlusions of central nervous system vessels. Three other members of her family were studied. Fabry’s disease (angiokeratoma corporis diffusum) is included among the rare causes of ischemic stroke in young adults.